Bacillus Fermentation of Soybean: A Review - Shrestha, Ashok Kumar; Dahal, Nawa Raj; Ndungutse, Vedaste (Journal of Food Science and Technology Nepal, 2013)
Soybeans in its natural form have a little direct use as a food due to its poor digestibility as well as beany taste and flavour. Fermentation; however, can improve the eating and nutritional qualities of soybeans. Fermented soybean foods have been an intricate part of oriental diet for a long time. Bacillus subtilis dominated traditionally fermented soyfoods have typical taste, texture and aroma which is popular in Asian and African countries. B. subtilis fermentation of soaked and cooked soybeans brings many physico-chemicals and sensory changes that make it highly digestible and nutritious. This paper reviews various facets of B. subtilis fermented traditional foods, properties of fermenting organisms, preparation of such fermented foods, changes in chemical composition and nutritional properties and improving the quality of these foods. J. Food Sci. Technol. Nepal, Vol. 6 (1-9), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8252